2021
DOI: 10.1016/j.celrep.2021.109162
|View full text |Cite
|
Sign up to set email alerts
|

Non-autonomous regulation of germline stem cell proliferation by somatic MPK-1/MAPK activity in C. elegans

Abstract: Highlights d Germline MPK-1B is dispensable for proliferation of germline stem cells d Germline MPK-1B is essential for gametogenesis and fertility d Somatic MPK-1A is required for a high rate of GSC proliferation d Somatic MPK-1A promotes germline proliferation from the gut or somatic gonad

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…This is possibly due to the similarity between the coding sequences of iff-1 and its somatic ortholog iff-2 , resulting in the RNAi targeting both transcripts. It is also possible that reduction of translation in the germline has cell non-autonomous effects to signal reduction of translation in other tissues ( Lan et al., 2019 ; Robinson-Thiewes et al., 2021 ). Knockdown of either iff-1 or ifg-1 resulted in similar decreases in OPP incorporation across the whole worm ( Figure 3 H), despite having different roles promoting translation initiation and translation elongation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to the similarity between the coding sequences of iff-1 and its somatic ortholog iff-2 , resulting in the RNAi targeting both transcripts. It is also possible that reduction of translation in the germline has cell non-autonomous effects to signal reduction of translation in other tissues ( Lan et al., 2019 ; Robinson-Thiewes et al., 2021 ). Knockdown of either iff-1 or ifg-1 resulted in similar decreases in OPP incorporation across the whole worm ( Figure 3 H), despite having different roles promoting translation initiation and translation elongation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, the DDR in germ cells also influences the soma such as elevating somatic endurance amid unrepaired meiotic DNA damage (Ermolaeva et al, 2013; Soltanmohammadi et al, 2022). Furthermore, endocrine signals have been observed to non-cell-autonomously influence stem cell proliferation and the DDR in mammals and C. elegans (Cinat et al, 2021; Gronke et al, 2019; Robinson-Thiewes et al, 2021; Xuefeng Chen, et al, 2011; Zhang et al, 2019). Somatic signaling cues are important for germline development and determine epigenetic memories that can last through several generations.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the presence of sperm, through release of MSPs, promotes oocyte ovulation, maintaining a high oocyte demand. This presumably activates MPK-1/ERK in the animal’s gut and/or somatic gonad, which nonautonomously promotes GSC proliferation, and sustains an elevated niche output and oocyte production [ 41 ]. (B) When sperm is depleted, ovulation is suppressed and oocytes initially accumulate in the proximal gonad, thereby reducing the demand for new oocytes.…”
Section: Regulation Of Stem Cell Proliferation Ratesmentioning
confidence: 99%
“…elegans hermaphrodites despite their sustained feeding and systemically activated IIS [ 34 , 35 ]. Genetic and epistasis analyses revealed that ERK/MAPK signaling promoted GSC proliferation in parallel to IIS and that the localized homeostatic regulation relied on ERK/MAPK suppression to inhibit GSC proliferation [ 35 , 41 ]. As such, nutrition through IIS and homeostatic signaling through ERK/MAPK act in concert to promote the highest levels of GSC proliferation in C .…”
Section: Regulation Of Stem Cell Proliferation Ratesmentioning
confidence: 99%
See 1 more Smart Citation